Characterisation of dynamic cellular processes in human stem cell models of inherited cardiomyopathy using genetically encoded reporters - Broyles, CN (2019)
The demonstrated number 1 killer in the world is cardiovascular disease, with inherited cardiomyopathies the more dramatic scenario as children are forced to live with the condition from an early age. Small genetic changes to the myofilament proteins in cardiac myocytes can result in either hypertrophic cardiomyopathy where the heart becomes enlarged and fails to relax efficiently, or dilated cardiomyopathy where the chambers of the heart stretch and are unable to appropriately contract. Either case results in inefficient delivery of vital oxygen and nutrients to the body. However it is not simply that one gene causes hypertrophy or dilation, but rather that single mutations within the same gene can cause either disease. This complicates how the diseases are understood, and the search for treatments. To address this, individual mutations must be investigated and specific molecular pathologies known, in order to effectively target the true problem when managing the condition; forcing researchers to focus on individual families containing the mutation, resulting in personalised approaches to medical treatment.